Family Support for the Independence of Children with Special Needs for Self-Care: Literature Review - Pursitasari, Ita (The Center for Disability Studies and Services Brawijaya University, 2019)
Children with Special Needs are children who have long-term problems on the physical or mental causes a child unable to carry out daily activities and interact with other people in the community (Cavallo, 2009). The limitations experienced by Them cause problems in self-care which result in health problems. So They can live quality, especially in terms of self-care needed support from his family. The goal is to find out family support for the independence of children with special needs in carrying out self-care. The method used is literature by taking some of the results of previous research from several scientific articles in the journal. The results of the literature review show that there is a need for parental support to establish children with special needs in carrying out self-care.